Analisis Spasial Potensi Genangan Banjir Rob Akibat Kenaikan Muka Air Laut di Pesisir Utara Kabupaten Gresik - Rayhan Al Dzikra; Vita Ayu Kusuma Dewi (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2026)
Sea level rise is an inevitable global phenomenon driven by global warming and climate change, mainly caused by polar ice melt and thermal expansion of seawater that increase ocean volume worldwide. When combined with local coastal factors such as tidal dynamics, land use change, and land subsidence, this process significantly elevates the risk of tidal flooding in low-lying coastal zones. This study aims to analyze the spatial distribution of tidal flooding along the northern coast of Gresik Regency, Indonesia. The analysis integrates a Digital Elevation Model (DEM), sea tide records from 2020 to 2025, land use data, and administrative boundary maps. Tide data were processed using the Least Square method with the PasutUGM14 application to derive the Highest High Water Level (HHWL) as the main parameter. Geographic Information System (GIS)-based spatial analysis was applied to simulate inundation and identify affected land use types. Results indicate sea level rise of 7–8 cm over five years, with a maximum HHWL of 1.019 m in 2024–2025. Modeling shows about 4,751.08 ha of coastal land are potentially exposed to tidal flooding, mainly affecting aquaculture ponds, swamps, mangrove forests, rice fields, and residential areas.